Silicification of wood adopted for barrel production using pure silicon alkoxides in gas phase to avoid microbial colonisation. (February 2015) - Guzzon, Raffaele; Widmann, Giacomo; Bertoldi, Daniela; Nardin, Tiziana; Callone, Emanuela; Nicolini, Giorgio; Larcher, Roberto
Abstract: The paper presents a new approach, covering wood with silica-based material in order to protect it from spoilage due to microbial colonisation and avoiding the loss of the natural features of the wood. Wood specimens derived from wine barrels were treated with methyltriethoxysilane in gas phase, leading to the deposition of a silica nanofilm on the surface. 29 Si and 13 C solid state Nuclear Magnetic Resonance and Scanning Electron Microscope–Energy Dispersive X-ray analysis observations showed the formation of a silica polymeric film on the wood samples, directly bonding with the wood constituents. Inductively Coupled Plasma-Mass Spectroscopy quantification of Si showed a direct correlation between the treatment time and silica deposition on the surface of the wood. The silica-coated wood counteracted colonisation by the main wine spoilage microorganisms, without altering the migration from wood to wine of 21 simple phenols measured using a HPLC-Electrochemical Coulometric Detection. Highlights: We synthesize a composite material by coating of barrel wood with methyltriethoxysilane by a gas-phase reaction. The material was characterized using a wide range of analytical and microbiological approaches. The silica layer discourages microbial contamination of wood reducing risks of wine spoilage. The silica layer showed a micro porosity able to allows chemical exchange between wood and wine.